K Jurnal Ilmiah: Kemampuan Menulis Teks Resensi Cerpen Siswa Kelas XI SMA Negeri 4 Kota Bengkulu - Lestari, Kurnia; Wulandari, Catur; Utomo, Padi (UNIB Press, 2022)
This study aims to describe the ability to write short story review texts for class XI students of SMA Negeri 4 Bengkulu City. The method used in this study is a descriptive method with a quantitative approach. The research sample amounted to 60 students from the total population. The sampling technique applied is random sampling. The data collection used was a test technique in the form of assigning students to write a review of the short story Pustaka Papa by Yovi Guantara Tanjung. The results showed that the students' ability to write short story reviews was good with an average score of 71.12. In the aspect of structure is quite adequate with the average score obtained by students 23.11, aspects of sentence use are classified as good with an average value of 16.40, aspects of word selection or diction are classified as good with an average value of 15.72, aspects of spelling use are classified as enough with an average value of 15.82.